Programming Python : powerful object-oriented programming - Lutz, Mark, ....- (Sebastopol : O'reilly, 2010)
Once you've come to grips with the core Python language, learning how to build Python applications presents a far more interesting challenge. Tap this book's wealth of practical advice, snippets of code, and patterns of program design to take your Python skills to the next level. You'll start with in-depth discussions of core concepts and then progress toward complete programs in different application domains, including: * GUI programming * Internet scripting * Parallel processing * Database management * Networked applications * System administration * Text processing Most programming experts consider this classic book, now updated for Python 3.x, to be the industry standard for learning Python application programming. With clear and concise explanations of Python syntax and programming techniques, and numerous examples that illustrate both correct usage and common idioms, Programming Python shows you the right way to code with Python.
Keywords: Computer; Programmeren; Software